The barn - Rogers, Leah H. (Candlewick Press, 2021)
One hundred years ago, many hands raised a red-cedar barn. Now the barn stands tall, smelling of freshly cut hay and dusty horses. As the animals wake and wander through its weathered doors, the barn watches the day unfold. Chickens peck, cows shoo flies with swishing tails, swallows fly in and out, and a cat crouches in the grass to hunt for dinner. When peepers start their evening song and the animals settle in their bedding again--the horses in their stalls, the cows in their pen, the swallows in their nests--the barn settles, too, until morning, when it gets to live the day all over again. Written by a debut author and narrated by the barnyard's serene sentinel, this lyrical and beautifully illustrated introduction to farm life is also a gentle way to wind down to bedtime.